Writing Literature Reviews in the Health Sector on an Ongoing Basis - Heru Santoso Wahito Nugroho; Cut Aja Nuraskin (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2022)
Literature review which is carried out systematically, it is very possible to be updated again, in accordance with the latest developments of the related research object. Thus, developments about the object from time to time are followed, so that a more solid understanding of the object can be obtained. Keywords: Literature review; ongoing; health sector